Clinician Maladaptive Anxious Avoidance in the Context of Implementation of Evidence-Based Interventions: A Commentary - Becker-Haimes, Emily M.; Klein, Corinna C.; Frank, Hannah E.; Oquendo, Maria A.; Jager-Hyman, Shari; Brown, Gregory K.; Brady, Megan; Barnett, Miya L. (Frontiers in Health Services, 2022)
This paper posits that a clinician's own anxious reaction to delivering specific evidence-based interventions (EBIs) should be better accounted for within implementation science frameworks. A key next step for implementation science is to delineate the causal processes most likely to influence successful implementation of evidence-based interventions (EBIs). This is critical for being able to develop tailored implementation strategies that specifically target mechanisms by which implementation succeeds or fails. First, we review the literature on specific EBIs that may act as negatively valenced stimuli for clinicians, leading to a process of clinician maladaptive anxious avoidance that can negatively impact EBI delivery. In the following sections, we argue that there are certain EBIs that can cause emotional distress or discomfort in a clinician, related to either: (1) a clinicians' fear of the real or predicted short-term distress the EBI can cause patients, or (2) fears that the clinician will inadvertently cause the patient harm and/or face liability. This distress experienced by the clinician can perpetuate a cycle of maladaptive anxious avoidance by the clinician, contributing to lack of or suboptimal EBI implementation. We illustrate how this cycle of maladaptive anxious avoidance can influence implementation by providing several examples from leading EBIs in the psychosocial literature. To conclude, we discuss how leveraging decades of treatment literature aimed at mitigating maladaptive anxious avoidance can inform the design of more tailored and effective implementation strategies for EBIs that are negatively valenced.